Synthesis of fluorinated diphenyl-diketopyrrolopyrrole derivatives as new building blocks for conjugated copolymers. Issue 19 (25th April 2016) - Jiang, Bin; Du, Chen Chen; Li, Min Jie; Gao, Ke; Kou, Li; Chen, Ming; Liu, Feng; Russell, Thomas P.; Wang, Hongyu
Abstract : A series of conjugated copolymers with an identical backbone (PBDT-DPP) but different fluorination numbers and positions were synthesized, and the impact of fluorine atoms on the structure–property-device performance was comprehensively investigated. Abstract : By varying the fluorine atom number and position, four novel fluorinated diphenyl-diketopyrrolopyrrole compounds, o -fDPP, o -ffDPP, m -fDPP, and m -ffDPP, were designed and synthesized. These key building blocks were then used to construct polymers with the benzo[1, 2- b :4, 5- b ′]dithiophene (BDT) donor moiety. Using this new system a systematic study to compare the numbers and positions of fluorine decoration was performed to understand their effect on the electronic properties, morphology and solar cell device performance. In comparison with the parent, non-fluorinated polymer, meta -fluorinated polymers showed a red-shift in the absorption, whereas such a shift was minimal for the ortho -fluorinated polymers. On introducing fluorine atoms into diphenyl-diketopyrrolopyrrole only a very small influence on both the HOMO and LUMO energy levels was observed, which was verified by theoretical calculations. However, fluorination can influence the planarity of the backbone, by introducing F⋯S interactions. Grazing incidence X-ray diffraction (GIXD) showed that meta -fluorinated polymers had an enhanced crystal size, while ortho -fluorinated polymers were less crystalline, in comparison with the non-fluorinated polymer. Resonant soft X-ray scattering (RSoXS) showed that fluorinated polymer:PC71 BM blends tended to form larger phase separated domains, leading to a smaller J sc than that of the non-fluorinated analogue. The photovoltaic performance results were corroborated with the electrochemical and morphological characterization of these polymers. Consequently, theP m -fDPP -based device exhibited the highest PCE of 1.40% among the fluorinated polymers. Although theP m -fDPP -based device had slightly larger V oc and FF values than that of non-fluorinatedPDPP, the overall device performance was lower than that ofPDPP (1.7%) because of the smaller J sc .